Body Style - Winge, Theresa M. (Subcultural style series, 2012)
"Body Style reveals the subcultural body as a site for understanding subcultural identity, resistance, agency and fashion. Analyzed, theorized, politicized, and sensationalized, the subcultural body functions as a framework where individuals build a sense of self and subcultural identity. Drawing on specific subcultural examples and interviews with subculture members, Body Style explores the subcultural body and its style within global culture. Body Style is the result of over eleven years of research examining these intersections within specific urban subcultures, including Urban Tribalists, Modern Primitives, Punks, Cybers, Industrials, Skates, and others. Divided into three main sections on subcultural body history, subcultural body identity and subcultural body styles, this book will be of particular interest to students of dress and fashion as well as those coming to subculture from sociology and cultural studies"-- Provided by publisher.